An empirical study on the internet usage among young creative entrepreneurs in Malaysia: A structural equation modeling approach - Ilham Sentosa; Aimi Zulhazmi Abdul Rashid; Sheikh Muhamad Hizam; Weni Hawariyuni (Proceedings of AICS - Social Sciences, 2017)
The present study seeks to examine empirically the antecedents of internet intention and adoption of young creative entrepreneur by applying the conceptual theory of technology acceptance model (TAM). There were 237 respondents indicated as young entrepreneur in the creative industries in Malaysia. A close ended questionnaire was designed to tap into the owner’s perception on perceived usefulness of the internet, perceived ease of use of the internet, and perceived credibility on the internet technology, intention to use the latest technology and adoption of the current internet for the business itself. Seven hypothesised relationships were tested in the structural model of internet adoption. Structural Equation Modeling (SEM) using AMOS 24.00 was conducted to establish and validate a hypothesised model. The data was analysed using path analysis of structural equation modeling (SEM) to test the causal and mediating effects amongst exogenous and endogenous variables. Based on the analysis and goodness of model fit, the hypothesised model and its findings supported the TAM theory extremely and all the hypothesised paths were asserted. The generated model found three significant positive and direct paths between perceived usefulness, perceived credibility and intention as well as between intention and adoption. The re-specified model produces two significant positive and direct significant paths (perceived usefulness to intention and intention to adoption) and also introduces three new paths (direct paths from perceived usefulness, perceived ease of use and perceived credibility to adoption). The fundamental of internet adoption models also manage to establish a mediating effects of intention on the said relationships between exogenous and endogenous of internet adoption among young creative entrepreneur. The finding is discussed in the context of entrepreneur intention and adoption of the internet in Malaysia.